Doravirine Exposure Decreased by Dialysis in a HIV Patient: A Grand Round. Issue 2 (11th April 2023) - Fromage, Yeleen; Codde, Cyrielle; Monchaud, Caroline; Labriffe, Marc; Lê, Minh P.; Faucher, Jean-François; Woillard, Jean-Baptiste
Abstract : Background: The authors report the case of a 66-year-old male patient who was hemodialyzed 3 times per week for chronic renal failure and treated with 100 mg of doravirine once daily in combination with dolutegravir for HIV-1. No dose adjustment is required for doravirine in cases of severe renal injury, but the effect of dialysis on its exposure is poorly understood. Methods & Results: Two series of 2 samples were drawn before and after 4-hour hemodialysis and showed an average doravirine concentration decrease of 48.1 ± 6.7%. The effects of hemodialysis were important, contrary to what was expected and has been previously reported. In addition, intraindividual variability was low. Nevertheless, because the concentrations reported were largely above the inhibitory concentration 50 (IC50 ), no dose adjustment was required. Conclusions: The decrease in doravirine concentration due to hemodialysis observed in this case report was quite significant. Therefore, therapeutic drug monitoring might be recommended in certain patients undergoing doravirine treatment also on hemodialysis.